Post-partum uterine prolapse in a bitch - HONPARKHE, M; SINGLA, V K; SINGH, JAGIR; BEDI, M; SATHYA, A (The Indian Journal of Animal Reproduction, 2023)
A rare case of canine post-partum prolapse and its treatment is documented.
Keywords: Bitch; post-partum; prolapse